2001
DOI: 10.1063/1.1330254
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical strain and damage in Si implanted with O and N ions at elevated temperatures: Evidence of ion beam induced annealing

Abstract: The accumulation of damage and the development of mechanical strain in crystalline Si ͑c-Si͒ by O and N ion implantation to doses up to 4ϫ10 17 cm Ϫ2 at elevated temperatures have been studied using Rutherford backscattering spectrometry and high resolution x-ray diffraction. The implantation of O or N ions at high temperatures produces two distinct layers in the implanted c-Si: ͑i͒ a practically damage-free layer extending from the surface up to Ӎ half of the depth of the mean projected range (R p ) and prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 12 publications
1
8
0
Order By: Relevance
“…The thickness of the a-Si layer is approximately 300 nm. In accordance with previous studies, 19,20 the near surface region ͑until the depth of ϳ150 nm in the present case͒ is apparently defect free after a high temperature implantation. In fact, this region accumulates a high density of vacancy clusters as a result of the ion implantation conditions, leading to the appearance of a localized mechanical strain in the crystal lattice.…”
Section: Resultssupporting
confidence: 80%
“…The thickness of the a-Si layer is approximately 300 nm. In accordance with previous studies, 19,20 the near surface region ͑until the depth of ϳ150 nm in the present case͒ is apparently defect free after a high temperature implantation. In fact, this region accumulates a high density of vacancy clusters as a result of the ion implantation conditions, leading to the appearance of a localized mechanical strain in the crystal lattice.…”
Section: Resultssupporting
confidence: 80%
“…It has also been reported that the damage profiles created by high-dose oxygen and nitrogen implantations at elevated temperatures ($600 C) shifted to large depths with respect to the distribution of energy deposited in nuclear collision. 24) The defects acting as gettering centers in the R p =2 region are ascribed to excess vacancies or vacancy-related defects [15][16][17][18]25) by referring to the distribution of excess vacancies in the near surface region. In fact, Peeva et al 25) have detected the vacancy-type defect formation in this region of Si-and He-ion implanted and annealed Si by TEM observations, although the point-defect profiles obtained by simulation (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The native SiO 2 layer was removed in diluted HF just before implantation. In the Si samples, a 150 nm deep vacancyrich layer was first formed by O + 2 or N + 2 ion implantation at 240 keV using a dose of 2.5 × 10 16 cm −2 at 400 • C [12,13]. Following this pre-implantation, Sb + was implanted at 20 keV to a dose of 5 × 10 14 cm −2 at room temperature.…”
Section: Methodsmentioning
confidence: 99%
“…Vacancies are usually formed during ion implantation. de Souza et al [12,13] have shown that during high temperature ion implantation in Si there are chemical effects associated with the defect formation process depending on the ion species used in the implantation (N, O, Ne or Mg). For instance, N-implanted samples presented higher compressive strain in the near surface region than O-implanted ones, which was associated with a higher vacancy concentration.…”
Section: Introductionmentioning
confidence: 99%